Communication Technologies and Aid Practices: Superbergamo, Group Chats, and the COVID-19 Pandemic - Parolin, Laura Lucia; Pellegrinelli, Carmen (Frontiers in Communication, 2022)
This article examines ‘Superbergamo’, a group that emerged in response to the needs of vulnerable citizens during the first wave of the Covid-19 pandemic in Bergamo (Italy). The analysis reveals the central role of social media and group chat systems in facilitating the spontaneous creation of the group, and the subsequent development of coordinated voluntary emergency activities that brought aid to thousands of local people. Inspired by Actor-Network theory, the analysis traces the group's emergence, showing how human and non-human actors – including social media and group chat apps - played a crucial role in shaping the aid practice. In so doing, we contribute to the literature on emergency responses from the public and social media. More significantly, we show how the critical contribution of technology to the development and sustenance of aid practices can be mapped, by providing evidence of how groups, practices and sociomaterial networks are necessarily entangled.